Anterior Segment Findings in Ocular Myocysticercosis in Children: Is it non- specific? - Singh, Prabhakar; Gupta, Abhishek; Gupta, Richa (Nepalese Journal of Ophthalmology, 2021)
Ocular cysticercosis is a preventable cause of blindness. Medical therapy has been recommended for the retro-orbital and extraocular muscle form. Surgical management is largely done in cases with conjunctival or lid affliction. Though, the medical management is simple; however, the diagnosis is challenging. The anterior segment findings often mimic the more common pathologies and hence often missed at the early stage. This case series of 3 pediatric patients, tries to highlight certain clinical clues which are suggestive of ocular myocysticercosis in children. Literature often recalls anterior segment findings in ocular myocysticercosis as “non- specific and nondiagnostic”. Canthal congestion and contiguous conjunctival congestion extending upto corresponding limbal border in absence of anterior chamber inflammation with other clinical clues are very suggestive of corresponding recti myocysticercosis.